Efficacy and safety of gemcitabine plus S-1 vs. gemcitabine plus nab-paclitaxel in treatment-naïve advanced pancreatic ductal adenocarcinoma - Zhou Zhu; Hui Tang; Jinrong Ying; Yuejuan Cheng; Xiang Wang; Yingyi Wang; Chunmei Bai (Cancer Biology & Medicine, 2023)
Objective: Gemcitabine plus nab-paclitaxel (GnP) is the standard first-line therapy for advanced pancreatic ductal adenocarcinoma (PDAC). S-1, an oral fluoropyrimidine derivative, as compared with gemcitabine, is non-inferior in terms of overall survival (OS) and is associated with lower hematologic toxicity. Accordingly, S-1 is a convenient oral alternative treatment for advanced PDAC. This study was aimed at comparing the efficacy and safety of gemcitabine plus S-1 (GS) vs. GnP as first-line chemotherapy for advanced PDAC. Methods: Patients with advanced PDAC who received first-line GS or GnP at the Peking Union Medical College Hospital between March 2011 and November 2022 were evaluated. Results: A total of 300 patients were assessed, of whom 84 received GS and 216 received GnP. The chemotherapy completion rate was higher with GS than GnP (50.0% vs. 30.3%, P = 0.0028). The objective response rate (ORR) was slightly higher (14.3% vs. 9.7%, P = 0.35), and the median OS was significantly longer (17.9 months vs. 13.3 months, P = 0.0078), in the GS group than the GnP group. However, the median progression-free survival (PFS) did not significantly differ between groups. Leukopenia risk was significantly lower in the GS group than the GnP group (14.9% vs. 28.1%, P = 0.049). Conclusions: As first-line chemotherapy for advanced PDAC, the GS regimen led to a significantly longer OS than the GnP regimen. The PFS, ORR, and incidence of severe adverse events were comparable between the GS and GnP groups.